2011
DOI: 10.1021/nl102878b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Radiative Rate in III−V Semiconductor Plasmonic Core−Shell Nanowire Resonators

Abstract: We investigate the radiative properties of plasmonic core-shell nanowire resonators and, using boundary element method calculations, demonstrate enhanced radiative decay rate by up to 3500 times in nanoscale compound semiconductor/metal cavities. Calculation of the local density of optical states enables identification of new types of modes in cavities with mode volumes on the order of 10(-4)(λ/n)(3). These modes dramatically enhance the radiative decay rate and significantly modify the polarization of far-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…This was reconsidered in an investigation into the modal properties of hybrid plasmonic waveguides [130]. We must also note that Atwater's group studied the influence of a plasmonic core/shell nanowire resonator on the Purcell factor of a III-V semiconductor nanowire [39]. Bian et al conducted further theoretical studies on nanowire-based hybrid plasmonic structures for low-threshold lasing, well below the wavelength scale [10].…”
Section: (B) Hybrid Systems and Heterostructuresmentioning
confidence: 99%
“…This was reconsidered in an investigation into the modal properties of hybrid plasmonic waveguides [130]. We must also note that Atwater's group studied the influence of a plasmonic core/shell nanowire resonator on the Purcell factor of a III-V semiconductor nanowire [39]. Bian et al conducted further theoretical studies on nanowire-based hybrid plasmonic structures for low-threshold lasing, well below the wavelength scale [10].…”
Section: (B) Hybrid Systems and Heterostructuresmentioning
confidence: 99%
“…A number of experiments have demonstrated that these cavities have a significant Purcell factor [4,10]. Others have also pointed out that these cavities can have high Purcell factors over a broad bandwidth and that even for light-emitting diode applications they are interesting [16]. (iii) Transfer to various substrates.…”
Section: Propagating Mode Cavity Disadvantagesmentioning
confidence: 99%
“…Considering that semiconductor gains can reach several thousands per centimeter, there is room to make devices where a large proportion of the lasing mode energy is coupled out. Others have also indicated that for both lasers and LEDs, such pillar structures can in theory have quite acceptable efficiencies, in the order of 50% [16,21]. For the propagating mode devices, controllable out coupling is achieved by adjusting the transmission characteristic of one of the mirrors, which with a metal mirror means controlling its thickness [17].…”
Section: Efficiency and Output Beam Qualitymentioning
confidence: 99%
“…Moreover, in many cases, for a relatively small modal volume, the optical modes of conventional cavities cannot match the modes to form the plasmon polaritons required by momentum and energy conservation for the efficient coupling. In contrast, plasmonic resonant cavities are capable of confining light at the nanometer scale, which leads to both enhanced local electromagnetic fields [5][6][7][8][9] and low mode volumes, [1,[9][10][11][12] and suggest promising applications for subwavelength optics and nanolasers, [13][14][15][16] nanoantennas, [17][18][19] sensing, [20][21][22][23] enhanced nonlinear effects, [18,[24][25][26][27] Surface enhanced Raman scattering, [8] and solar cell elements, [28,29] to name a few.…”
Section: Introductionmentioning
confidence: 99%